2006
DOI: 10.1111/j.1365-2516.2006.01347.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for factor XI deficiency amongst pregnant women of Ashkenazi Jewish origin

Abstract: A pilot study was conducted over a 6-month period to evaluate antenatal screening for factor XI (FXI) deficiency amongst Ashkenazi Jewish women booking for their pregnancy in a single obstetric unit. Fifty-four women of Ashkenazi Jewish origin were recruited during their visit for the routine first trimester ultrasound scan. They completed a questionnaire about their personal bleeding symptoms and had blood taken for FXI levels (FXI:C). Seven (13%) women had partial FXI deficiency. Five (9%) were newly diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…A total of 268 women with FXI deficiency were included in ten studies (see Table ), in 56 of whom (21%) heavy menstrual bleeding was reported.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 268 women with FXI deficiency were included in ten studies (see Table ), in 56 of whom (21%) heavy menstrual bleeding was reported.…”
Section: Resultsmentioning
confidence: 99%
“…Studies describe patients as having either severe or non-severe (or partial or mild or heterozygote) FXI deficiency. The most frequently used definition classifies [14,15,17,18,[23][24][25]34] FXI <20 IU dL À1 as severe FXI deficiency and FXI between ≥20 IU dL À1 to <70 IU dL À1 as non-severe FXI deficiency.…”
Section: Classificationmentioning
confidence: 99%
See 3 more Smart Citations